Students’ Perception Towards the Use Of “Cake Application” As A Medium to Increase Vocabulary Knowledge - Nurhaliza, Sofia; Fakhurriana, Ria (LP2M Institut Agama Islam Negeri (IAIN) Kediri, 2023)
Vocabulary knowledge is considered an important tool in language learning. One piece of technology that may be used to learn foreign languages is the online learning application. In this day and age of digitalization, students may access resources through the internet. Due to this, this study focuses on using Cake as a tool to increase students' understanding of math concepts in middle school. The subjects of this study are 25 students who are currently learning English. The data is then analyzed using a descriptive analysis. Data collection is done using questionnaires and surveys. Students are given questionnaires and surveys related to alternative technologies for math education, such as the online Cake application. The study's findings indicate that the online Cake application can improve students' knowledge of vocabulary in the context of vocabulary practice. It is stated that the Cake web application might serve as one alternative to address the issue of word comprehension.